ANALISIS FAKTOR DETERMINAN YANG MEMPENGARUHI TINGKAT INFLASI DI INDONESIA DENGAN ERROR CORRECTION MECHANISM - Muhammad Basorudin; Ayu Fithri Maharani; Fitria Ramadhan; Stevanus Ronaldo (Universitas Dian Nuswantoro Semarang, 2019)
In general, inflation is considered an important problem that must be resolved given its serious effects such as an unstable economy, rising prices of goods, rising unemployment and other impacts. This study aims to determine the effect of Bank Indonesia Interest Rates on inflation in Indonesia and find out the effect of changes in the money supply in (M2) on inflation in Indonesia. The method used is Error Correction Mechanism (ECM). Based on the model it is known that the BI rate variable has a significant effect on inflation, meaning that the interest rates issued by Bank Indonesia affect the inflation rate in Indonesia. Then, the M2 Growth Rate variable has no significant effect on inflation. The coefficient value of (ECT (-1)) of -0,1921 shows that short-term equilibrium fluctuations will be corrected towards the equilibrium of the long equilibrium around 19.21%. The adjusment process occurs in the first month and the rest is an adjudication process that occurs in the following months.